Isolated vitamin E deficiency and progressive ataxia. Issue 5 (November 1993) - Rayner, R J; Doran, R; Roussounis, S H
Abstract : A case of progressive spinocerebellar syndrome due to isolated vitamin E deficiency is reported. Measurement of the vitamin E concentration in serum should be included when investigating all children with unexplained, progressive ataxia, even in the absence of malabsorption. Replacement treatment in patients with a vitamin E deficiency can arrest or improve the associated neurological disorder.